PET Findings in Tuberous Sclerosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
The clinical role of positron emission tomography (PET) was evaluated in 23 children with tuberous sclerosis complex examined at the Children's Hospital of Michigan, Wayne State University, Detroit, MI.